Combined anti-diabetic and wound healing effects of binahung leaf (Basella rubra L.) and snakehead fish (Channa striata) extracts in alloxan-induced high-fat diet rats - Sasongko, Heru; Muslimah, Intan; Ningsih, Sukmania Indra Alvianti; Sutarno, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Diabetes mellitus is a metabolic disease that continues to increase in the world. Lifestyle factors cause diabetes cases to increase uncontrollably. The development of medicines based on natural ingredients has become a subject of study for researchers throughout the world. Meanwhile, binahong leaf extract contains flavonoids and saponins, which can reduce the absorption of glucose. Snakehead fish extract containing albumin also influences the reduction of diabetic wounds. The combination of binahong and snakehead fish extract is expected to synergistically lower blood glucose levels and cure diabetic wounds. Therefore, this study aimed to determine the anti-diabetic and wound healing activity resulting from the combination of binahong leaf and snakehead fish extract in rat models of diabetes induced with alloxan and fat diet. The test animals were divided into six groups with five per group, namely normal, positive, and negative control, as well as dose 1 (snakehead fish 250 mg/kg and binahong extract 100 mg/kg), dose 2 (snakehead fish 250 mg/kg and binahong extract 300 mg/kg), and a single dose of snakehead fish extract 500 mg/kg. The experiment was conducted for 21 days by administering the test solution once a day. The results showed that administering a combination of binahong extract at a dose of 100 mg/kg and snakehead fish at a dose of 500 mg/kg significantly reduced blood glucose levels in diabetic rats (p≤0.05). Treatment using a combination of the two extracts was more effective in lowering blood sugar levels compared to a single dose of snakehead fish extract.